Investigation on hybrid split-capacitors and split-inductors applied in positive output luo-converters - Wang, Tao (2013)
An introduction on the fundamentals of split-capacitors and -inductors is given in this paper. Positive output Luo-converter is taken as the platform by which the integration of split-capacitors/inductors with the voltage lift technique is implemented successfully. The voltage transfer gains of the newly-derived DC-DC topologies are significantly increased along with the number increasing of split-capacitors and - inductors. The simulation results are provided to validate the topology analysis results.